Harnessing the Natural Pool of Polyketide and Non-ribosomal Peptide Family: A Route Map towards Novel Drug Development - Girija, Aiswarya; Vijayanathan, Mallika; Sreekumar, Sweda; Basheer, Jasim; Menon, Tara G; Krishnankutty, Radhakrishnan E; Soniya, Eppurathu V (Current molecular pharmacology, 2022)
The emergence of communicable and non-communicable diseases has posed a health challenge for millions of people worldwide and is a major threat to the economic and social development in the coming century. The occurrence of the recent pandemic, SARS-CoV-2, caused by lethal severe acute respiratory syndrome coronavirus 2, is one such example. Rapid research and development of drugs for the treatment and management of these diseases have become an incredibly challenging task for the pharmaceutical industry. Although, substantial attention has been paid to the discovery of therapeutic compounds from natural sources having significant medicinal potential, their synthesis has made a slow progress. Hence, the discovery of new targets by the application of the latest biotechnological and synthetic biology approaches is very much the need of the hour. Polyketides (PKs) and non-ribosomal peptides (NRPs) found in bacteria, fungi and plants are a diverse family of natural products synthesized by two classes of enzymes: polyketide synthases (PKS) and non-ribosomal peptide synthetases (NRPS). These enzymes possess immense biomedical potential due to their simple architecture, catalytic capacity, as well as diversity. With the advent of the latest in-silico and in-vitro strategies, these enzymes and their related metabolic pathways, if targeted, can contribute highly towards the biosynthesis of an array of potentially natural drug leads that have antagonist effects on biopolymers associated with various human diseases. In the face of the rising threat from multidrug-resistant pathogens, this will further open new avenues for the discovery of novel and improved drugs by combining natural and synthetic approaches. This review discusses the relevance of polyketides and non-ribosomal peptides and the improvement strategies for the development of their derivatives and scaffolds, and how they will be beneficial for future bioprospecting and drug discovery.
Keywords: Polyketides; Humans; NRPS; natural products; COVID-19 Drug Treatment; secondary metabolites; farmakoterapie COVID-19; bioactive molecules; vyvíjení léků; peptidy; SARS-CoV-2; polyketidy; lidé; Drug Development; Peptides